Uso de medicamentos psicoativos : um estudo com jovens que tentaram suicídio em Maringá - Rabelo, Juliana Furlan (2008)
The manner in which medications are used, especially psychoactive medications, plays an important role in promoting rational use of medications. The present study has as objective to analyze the use of psychoactive medications in suicide attempts by youngsters. This is a descriptive study, applying a case series design. The sample was composed of youngsters who had attempted suicide using psychoactive medications, with ages between 10 and 24, residing in Maringá-PR, enrolled in the Poison Control Center (CCI/HUM) of the Maringá Regional University Hospital, in the period from January to July 2008. Data was collected from Notification and Assistance Record Sheets of the CCI/HUM and two interview scripts, which differed based on the modality of psychoactive medication use: one for youngsters who attempted suicide psychoactive medications of their own, and another for youngsters had not used psychoactive medications. The scripts were applied in home visits, to a family member, preferably the mother. Quantitative data from the record sheet and the interview scripts were inserted in an Excel (2002) spreadsheet, and data from the patient's clinical history and information given by the family member interviewed were reported individually. The project received approval 463/2007 from the Ethics Committee on Human Research of the State University of Maringá. The results are presented in two stages: the first one describes the youngsters, their families an d the toxicological occurrences of the suicide attempt; and the second one, the access and availability of the psychoactive medications, according to the different modalities of use. The case of 17 youngsters were studied - mostly female, single, 15-24 years of age, with average monthly family income between 300 and 900 Reais (58.8%). In all cases, the site of the occurrence was the youngster's home, and the attempt was related to a conflict situation. The most often psychoactive medications used in the suicide attempts were antidepressants (47%). Twelve youngsters (70.6%) attempted suicide using their own psychoactive medications, and five with drugs used by another person. Separating the cases between the two modalities of use, a high availability of medications in the home setting was found in all cases. In 82.3% of cases, the psychoactive substances has been prescribed by a doctor; however, usage information were limited to the adequate dosage for the desired therapeutic effect, and the dispensing of the medication in the majority of cases, was done by the public health services in high quantities. The families reported the practice of selfmedication (47%), including of psychoactive medications, and signs of illegal acquisition of this type of medication were found in three cases. Large quantities of medications were stored in the home, stored in inadequate places (63.6% in the kitchen), providing easy access to the psychoactive medications. For youngsters who had not used psychoactive medications, in all cases the access was facilitated by a family member who used the medication. The instructions regarding correct use of the medication and the facilitated access in the home setting were similar between the two modalities of use.